2017
DOI: 10.1111/anu.12570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary bovine lactoferrin on growth, haemato-biochemical parameters, immune functions and tolerance to air exposure stress in the African cichlid Sciaenochromis fryeri

Abstract: The effects of dietary bovine lactoferrin (LF) on the growth, haemato-biochemical parameters, non-specific serum immunity and stress responses were investigated in the African cichlid, Sciaenochromis fryeri. Four isocaloric diets containing 0 (control), 200, 400 and 800 mg LF kg −1 diet were formulated and fed to juvenile fish for 8 weeks. The treatments had no effects on the survival rate, growth performance or haematological parameters. Nor were the serum levels of total protein, albumin and globulin signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…This study also demonstrated that fish fed 800 and 1200 mg/kg exhibited growth enhancement, whereas Moradian et al. (2018) reported high lysozyme and bactericidal activities in African cichlid ( Sciaenochromis fryeri ) fed bLF (200 and 800 mg/kg) respectively. Nevertheless, there were no effects on growth performance or physiological parameters, such as serum total protein and serum iron levels (Table 1).…”
Section: Features Of Blfsupporting
confidence: 56%
See 1 more Smart Citation
“…This study also demonstrated that fish fed 800 and 1200 mg/kg exhibited growth enhancement, whereas Moradian et al. (2018) reported high lysozyme and bactericidal activities in African cichlid ( Sciaenochromis fryeri ) fed bLF (200 and 800 mg/kg) respectively. Nevertheless, there were no effects on growth performance or physiological parameters, such as serum total protein and serum iron levels (Table 1).…”
Section: Features Of Blfsupporting
confidence: 56%
“…Additionally, orally administered bLF enhances tolerance to air exposure stress in the African cichlid (Moradian et al., 2018) and increases the level of HSP70 in the branchial lamellae of orange‐spotted grouper ( Epinephelus coioides ) exposed to low salinity (Yokoyama et al., 2006). Increasing dietary levels of bLF also result in an increased recovery rate from air exposure stress in spotted groupers.…”
Section: Features Of Blfmentioning
confidence: 99%
“…The antibacterial property of lactoferrin is attributed to its iron (an essential nutrient for bacterial growth) sequestering ability (Welker et al 2007). Moreover, administration of lactoferrin was found to improve tolerance to hypoxia stress in Cyprinus carpio (Kakuta 1998), nitrite stress in Macrobrachium rosenbergii (Chand et al 2006), air exposure stress in Sciaenochromis fryeri and Epinephelus coioides (Yokoyama et al 2006;Moradian et al 2018), low salinity stress in Epinephelus coioides and Seriola dumerili (Yokoyama et al 2006;Yokoyama et al 2019) and high-temperature stress in Paralichthys olivaceus (Yokoyama et al 2005). Hence, it could be concluded that dietary inclusion of lactoferrin is a viable nutritional strategy for aquaculture stress management.…”
Section: Biological Derivativesmentioning
confidence: 99%
“…2006; Moradian et al . 2018), low salinity stress in Epinephelus coioides and Seriola dumerili (Yokoyama et al . 2006; Yokoyama et al .…”
Section: Stress Mitigation Through Dietary Additives/nutraceuticalsmentioning
confidence: 99%
See 1 more Smart Citation